Working Capital Management and Profitability of Manufacturing Sector of Bangladesh: A Causal Relationship - Neelom, Kashfia Haque; Asad, Suzona (American Journal of Trade and Policy, 2017)
This paper explores the causal relationship between working capital management and corporate profitability of manufacturing sector of Bangladesh. Sample data is composed of 21, Dhaka Stock Exchange (DSE) listed companies of Bangladesh, of four different industries from the year 2011 to 2015. A multivariable model has been developed to examine the association between profitability and the working capital management. In the analysis, current ratio and debt ratio have been used as control variables. The findings clearly indicate a negative relationship between working capital management and profitability in the overall manufacturing sector as well as in each of these four industries and significance level varies from industry to industry.
Keywords: Working capital management; Cash conversion cycle; ROA